Association of Proinflammatory Cytokine Levels with Stroke Severity, Infarct Size, and Muscle Strength in the Acute Phase of Stroke - Bitencourt, Ana Carolina Silva; Timóteo, Rodolfo Pessato; Bazan, Rodrigo [UNESP]; Silva, Marcos Vinícius; da Silveira Filho, Luiz Gonzaga; Ratkevicius, Cristhianne Molinero Andrade; de Assunção, Thaís Soares Farnesi; de Oliveira, Ana Paula Silva; Luvizutto, Gustavo José (Elsevier, 2022)
Objective: Patterns of cytokine levels and their association with stroke severity, infarct size, and muscle strength are obscure. We aimed to analyze the immune mediators linked to T helper (Th)1, Th2, Th17, and regulatory T cell patterns and their association with stroke severity, infarct size, and muscle strength. Materials and methods: We included patients with acute stroke (n = 15) and healthy non-disabled individuals (n = 20) aged > 18 years. The dependent variables were stroke severity according to the National Institute of Health Stroke Scale (NIHSS), infarct size on computed tomography, handgrip strength by dynamometry, and global muscle strength according to the Medical Research Council (MRC) scale. The independent variables were the circulating cytokine levels. The cytokine levels were compared between the groups, and correlations between the clinical data were verified. Results: The stroke group had higher interleukin (IL)-6 (p < 0.0001) and IL-10 (p < 0.0001) levels, but lower tumor necrosis factor (TNF)-α (p = 0.036) levels than the control group. IL-10 and soluble tumor necrosis factor receptor (sTNF-RII) levels were correlated with each other (r = 0.533; p = 0.042) and infarct size (r = 0.653; p = 0.033 and r = 0.689; p = 0.018, respectively). MRC scores were positively and negatively correlated with handgrip strength of the affected side (r = 0.78; p = 0.001) and NIHSS scores (r = -0.87; p < 0.0001), respectively. Conclusions: Plasma levels of some cytokines were associated with changes in the acute phase of stroke, and IL-10 and sTNF-RII levels are potential biomarkers of infarct size.
Keywords: Acute stroke phase; Cytokines; Infarct size; Muscle strength; Stroke; Stroke severity